Peak head accelerations in elite rugby union players during match-play collisions: A preliminary study comparing males and females using instrumented mouthguards - Izri, E.; Brown, M. R.; Jones, C.; Kilduff, L. P.; Waldron, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The collision-dominant nature of rugby union exposes players to head acceleration events (HAEs), which are a potential risk factor for the development of brain injuries, such as concussion. Instrumented mouthguards enable direct measurement of the magnitude of these HAEs during training and competition. The differences in physical demands of the game, and physical characteristics of males and females, suggests that they might experience different magnitudes of head accelerations owing to a collision; however, this has not been investigated among elite rugby players. The aims of this preliminary study were to compare the magnitude of peak linear and angular head accelerations i) experienced by male vs. female players and ii) during head vs. body impacts.